Non-dispersive Fano resonances in hybrid plasmonic-distributed Bragg reflector structures - Wang Shuangshuang; Hu Huatian; Liu Xiaoze; Ding Tao (Nanophotonics, 2023)
Fano resonance due to coupling of plasmon mode and Bragg modes is revealed without strong angular dependence based on Au nanoparticle on distributed Bragg reflectors (Au NPoDBRs). This Fano interference involves three-modes-coupling: the nanoparticle’s plasmon resonance, dispersive Bragg modes, and non-dispersive Bragg modes. It can be interpreted as a consequence of two processes: plasmonic coupling between dispersive Bragg modes and broad plasmon mode, and the strong coupling between narrowed plasmonic mode and non-dispersive Bragg mode. This Fano interference shows little dependence on the incidence angle but high tunability with the top-layer thickness, which is exploitable for novel nanophotonic devices with dispersion engineering.